A break-even analysis of delivering a memory clinic by videoconferencing. (October 2013) - Comans, Tracy A; Martin-Khan, Melinda; Gray, Leonard C; Scuffham, Paul A
We analysed the costs of two kinds of dementia clinic. In the conventional clinic, held in a rural area, the specialist travels to the clinic from the city. In the videoconferencing clinic, patients are also seen in a rural area, but the specialist conducts the assessment by video from the city. The fixed costs common to both modalities, such as clinic infrastructure, were ignored. The total fixed cost of a monthly conventional clinic was 522 and the total fixed cost of a monthly videoconferencing clinic was 881. The additional variable cost of the specialist travelling to the conventional clinic was 2.62 per minute of the specialist's travelling time. The break-even point at which the cost of the two modalities is the same was just over two hours (138 min round trip). A sensitivity analysis showed that the break-even point was not particularly sensitive to changes in staff wages, but slightly more sensitive to the non labour costs of videoconferencing. Air travel is not an efficient alternative to travel by car. Reducing the number of clinics to six per year results in a much higher cost of running the videoconferencing service compared to the conventional service. Videoconferencing for the purpose of diagnosing dementia is both a reliable and cost effective method of health service provision when a specialist is required to drive for more than about two hours (round trip) to provide a memory disorder clinic service.